PSYCHOLOGICAL MECHANISMS OF DEVELOPMENT OF GENERAL TEACHING ACTIONS AT BIOADEQUATE STUDYING - Elena V. Nemolot (Открытое образование (Москва))
Scientific methodological basis of FSES is under consideration, the main point is general teaching action as showing of progress studying by a pupil. The opportunity of developing different kinds of general teaching actions at bioadequate studying with the help of psychological mechanisms is determined.